SLAMF9 aggravates myocardial ischemia reperfusion injury through activating the hippo-yap pathway - Liu, Tingting; Guo, Xiuli; Fu, Yanhua; Zhang, Weili (Biochimica et biophysica acta. General subjects, 2025)
The objective was to investigate the impact of signaling lymphocyte activation molecule family member 9 (SLAMF9) on myocardial infarction (MI) and its mechanisms. SLAMF9 expression in MI rats was firstly measured. SLAMF9 effect on cardiac functions, myocardial fibrosis, cardiomyocyte hypertrophy, cardiomyocyte apoptosis and inflammation in MI rats was explored using echocardiography, HE staining, masson staining, wheat germ agglutinin staining, western blot, TUNEL staining and qRT-PCR. Meanwhile, SLAMF9 effect on the viability, apoptosis, and inflammation in H9C2 cells was investigated by CCK-8 assay, TUNEL staining and western blot. Moreover, the potential mechanisms of SLAMF9 were investigated using western blot, ELISA and TUNEL staining after different treatment. SLAMF9 expression was upregulated in MI rats. SLAMF9 knockdown ameliorated heart damage, cardiomyocyte apoptosis and inflammatory response in MI rats. Similarly, SLAMF9 silencing in macrophages attenuated the apoptosis and inflammatory response in H/R-induced H9C2 cells. Moreover, SLAMF9 knockdown inhibited Hippo-Yap pathway in MI in vitro and in vivo. Besides, SLAMF9 knockdown in macrophages suppressed the activation of Hippo-Yap pathway in H9C2 cells by inhibiting TNF-α release. Additionally, LATS1 overexpression in H9C2 cells reversed the effect of SLAMF9 silencing on the apoptosis and inflammatory response in H/R-induced H9C2 cells. Meanwhile, PY-60 treatment in H9C2 cells reversed the effect of SLAMF9 overexpression on the apoptosis and inflammatory response in H/R-induced H9C2 cells. The absence of SLAMF9 led to a reduction in TNF-α secretion in macrophages, consequently repressing Hippo-Yap pathway in cardiomyocytes, and ultimately ameliorating myocardial damage, cardiomyocyte apoptosis and inflammation in MI. •SLAMF9 expression was upregulated in MI.•SLAMF9 knockdown ameliorated heart damage and inflammation in MI.•SLAMF9 knockdown inactivated Hippo-Yap pathway in MI.